Silver queendom - Koboldt, Dan (Daniel C.) (Angry Robot, an imprint of Watkins Media Ltd, 2022)
Darin, the innkeeper of the notorious Red Rooster Inn, is the leader of the best team of con artists in the Old Queendom. When he's approached to steal a shipment of imperial dreamwine, he knows he should turn the job down--but he has pressing financial needs. And so the crew begins to plot its heist of the most precious substance in the queendom.